We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
326
1
avatar+924 

The rule an=−2⋅3 n-1 is the explicit rule for a geometric sequence.

Which equation represents the recursive rule for this sequence?

 

an=3⋅an+1 , a1=−2

an=−2⋅an−1 , a1=−2

an=−2⋅3⋅ an−1 , a1=−2

an=3⋅an-1 , a1=−2

 Jan 8, 2019
 #1
avatar+100546 
+2

Let's list the first few terms

 

- 2, - 6, - 18, -54

 

Note that each succesive term is just 3 times the previous.....so....

 

The recursive rule is

 

an =  3* an-1, a1 = -2

 

 

cool cool cool

 Jan 8, 2019

3 Online Users